2019
DOI: 10.2478/boku-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of row spacing, seeding rate and nitrogen fertilization on yield and yield components of soybean

Abstract: Summary Soybean crop management have not been studied much in Central Europe as compared with cereals. We assessed the effect of variety, row spacing, seeding rate and nitrogen (N) fertilization on yields and yield components of soybean in a two-year experiment in Gleisdorf, Austria. The varieties Lenka, Naya and Xonia were tested in row spacings of 13 cm, 38 cm and 76 cm with 30 germinable seeds m−2. Additionally, 60 seeds m−2 were tested at 13 cm row spacing, and 38 cm row spacing was additionally establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Common fertilizer application methods, like banding fertilizer along a crop row or injecting it into the soil near crops, can reduce weed biomass relative to broadcasting, which was used in this experiment (Di Tomaso, 1995;Blackshaw et al, 2004). Furthermore, while high soybean density suppressed weeds and enhanced yields, there is a greater risk of disease (Hwang et al, 2006;Chang et al, 2011;Swoboda et al, 2011) and crop lodging (Costa et al, 1980;Neugschwandtner et al, 2019) in dense crop stands. Understanding how different management decisions affect weed communities and competition, as well as crop productivity and crop susceptibility to other pests, will enable the development of robust weed management strategies for organic no-till systems.…”
Section: Discussionmentioning
confidence: 99%
“…Common fertilizer application methods, like banding fertilizer along a crop row or injecting it into the soil near crops, can reduce weed biomass relative to broadcasting, which was used in this experiment (Di Tomaso, 1995;Blackshaw et al, 2004). Furthermore, while high soybean density suppressed weeds and enhanced yields, there is a greater risk of disease (Hwang et al, 2006;Chang et al, 2011;Swoboda et al, 2011) and crop lodging (Costa et al, 1980;Neugschwandtner et al, 2019) in dense crop stands. Understanding how different management decisions affect weed communities and competition, as well as crop productivity and crop susceptibility to other pests, will enable the development of robust weed management strategies for organic no-till systems.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) and Neugschwandtner et al. (2020) in different production areas, climate conditions, field management, and soybean maturity groups. The low yield components of soybean after ryegrass, kidney vetch, and corn cockle were induced by the reduced LAI as seen in experiments with low assimilation capacity by Board and Tan (1995) and Kantolic et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Neugschwandtner et al. (2020) showed that grain yield remained independent of plant density, row spacing, or fertilization and concluded that the ability of soybean yield formation compensates for the applied management practice. In the current study, the TKM was not affected by cover crop treatments (except after corn cockle in 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The numerically greatest first pod height was seen for the conventional system (17.4 cm) and the numerically lowest for the no-tillage system (13.1 cm). Soybean seed loss during harvesting is a major problem, and this has been related to first pod height [50,51]. First pod height is affected by the genetic structure, cultivation processes, and precipitation or irrigation levels [52].…”
Section: Soybean Yield Components and Dry Seed Productionmentioning
confidence: 99%